Mutant p53 Gain-of-Function: Role in Cancer Development, Progression, and Therapeutic Approaches - Alvarado-Ortiz, Eduardo; de la Cruz-López, Karen Griselda; Becerril-Rico, Jared; Sarabia-Sánchez, Miguel Angel; Ortiz-Sánchez, Elizabeth; García-Carrancá, Alejandro (Frontiers in Cell and Developmental Biology, 2021)
Frequent mutations of p53 (mutp53) not only abolish tumor suppressor capacities but confer gain-of-functions (GOF’s) that impact molecules and pathways now regarded as central for tumor development and progression. Although the complete impact of GOF’s are still far from being fully understood, their effects on proliferation, migration, metabolic reprogramming and immune evasion among others certainly constitute major driving forces for human tumors harboring them. In this review we discuss major molecular mechanisms driven by GOF’s of mutp53. We present novel mechanistic insights on their effects over key functional molecules and processes involved in cancer. We analyze new mechanistic insights impacting processes such as immune system evasion, metabolic reprogramming and stemness. In particular, the increased lipogenic activity through mevalonate pathway (MVA) and alteration of metabolic homeostasis due to interactions of mutp53 with AMPK and SREBP that impact anabolic pathways and favor metabolic reprograming. We address, in detail, the impact of mutp53 over the metabolic reprogramming and the Warburg effect observed in cancer cells as a consequence, not only of LOF of p53, but rather as an effect of GOF’s that are crucial for the imbalance between glycolysis and oxidative phosphorylation. Additionally, transcriptional activation of new targets, resulting from interaction of mutp53 with NF-kB, HIF1a, or SREBP, are presented and discussed. Finally, we discuss perspectives for targeting molecules and pathways involved in chemo-resistance of tumor cells resulting from mutp53 GOF. We discuss and stress the fact that the status of p53 constitutes, at this moment, one of the most relevant criteria to understand the role of autophagy as a survival mechanism in cancer, and propose new therapeutic approaches that could allow the reduction of GOF exercised by mutp53 in cancer.